2021
DOI: 10.3390/v13061001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Linda Virus Neutralizing Antibodies in the Austrian Pig Population

Abstract: A novel pestivirus species, termed Lateral-shaking Inducing Neuro-Degenerative Agent virus (LindaV), was discovered in a piglet-producing farm in Austria in 2015 related to severe congenital tremor cases. Since the initial outbreak LindaV has not been found anywhere else. In this study, we determined the seroprevalence of LindaV infections in the domestic pig population of Austria. A fluorophore labeled infectious cDNA clone of LindaV (mCherry-LindaV) was generated and used in serum virus neutralization (SVN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…However, the virus persisted in lymphoid tissues and was still detectable after 21 days. To date, LindaV has been detected in the index case as well as in a farm 10 km away as a consequence of a nationwide screening for LindaV neutralizing antibodies [16]. This study revealed a very low seroprevalence of 0.15% (based on the number of sera screened) and 0.7% (at farm level) in Austria [16].…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…However, the virus persisted in lymphoid tissues and was still detectable after 21 days. To date, LindaV has been detected in the index case as well as in a farm 10 km away as a consequence of a nationwide screening for LindaV neutralizing antibodies [16]. This study revealed a very low seroprevalence of 0.15% (based on the number of sera screened) and 0.7% (at farm level) in Austria [16].…”
Section: Introductionmentioning
confidence: 73%
“…This study revealed a very low seroprevalence of 0.15% (based on the number of sera screened) and 0.7% (at farm level) in Austria [16]. A novel, genetically closely related LindaV strain (LindaV strain Austria2) could be isolated from a serum sample in 2016 [16]. Interestingly, clinical signs of CT had never occurred in pigs of that farm, according to the farmer and responsible veterinarian.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…E2 fusion protein reporter viruses showed stronger reporter activity because the E2 is stable and accumulates in infected cells. Such an E2 reporter pestivirus was recently used in serological assays to determine LINDA pestivirus seroprevalence [ 48 ]. Considering that cp pestiviruses have much stronger protein expression than ncp pestiviruses, we hypothesized that reporter activity for E2 reporter genes would be further increased in the context of cp viruses.…”
Section: Introductionmentioning
confidence: 99%